2015
DOI: 10.1007/s12032-015-0680-1
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized clinical trial comparing D2 dissection in laparoscopic and open gastrectomy for gastric cancer

Abstract: Laparoscopic surgery is an acceptable alternative to open surgery in colorectal cancer treatment. However, in gastric cancer, there is not much scientific evidence. Here, we proposed a prospective randomized clinical trial to evaluate the radicalness and safety of laparoscopic D2 dissection for gastric cancer. From October 2010 to September 2012, 300 patients with gastric cancer were randomized to undergo either laparoscopy-assisted gastrectomy (LAG) or conventional open gastrectomy (OG) with D2 dissection. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 30 publications
1
51
0
4
Order By: Relevance
“…Also, we checked the references of relevant reviews, published meta‐analyses and possible included studies. Finally, 14 RCTs totaling 2,307 gastric cancer survivors (1,163 laparoscopic and 1,144 open) were included in present meta‐analysis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, we checked the references of relevant reviews, published meta‐analyses and possible included studies. Finally, 14 RCTs totaling 2,307 gastric cancer survivors (1,163 laparoscopic and 1,144 open) were included in present meta‐analysis .…”
Section: Resultsmentioning
confidence: 99%
“…Although blinding was seldom described in most studies, outcomes of interest seemed to be difficult to be influenced by the lack of blinding. Overall, two trials were categorized as at low risk of bias and twelve as at unclear risk of bias .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In East Asia, large-scale, multicenter RCTs are currently ongoing not only in Japan, but also in Korea (KLASS 02: NCT01456598) and China (CLASS 01: NCT01609309). Regarding to short-term outcome from the Chinese trials including CLASS01 study, favorable outcome in LADG as well as ODG for AGC has been demonstrated (30,31). These data in combination will be beneficial for determining the role of LAG.…”
Section: Current Studies Of Ladg For Advanced Gastric Cancer (Agc)mentioning
confidence: 97%
“…8 Several other series of single institution experiences have been reported from Asia and Western Europe. In addition, two recent prospective randomized trials have shown technical safety of laparoscopic-assisted distal gastrectomy in Japan 9 and laparoscopic-assisted gastrectomy in China, 10 including 42 total gastrectomies with D2 lymphadenectomy. Both trials showed safety and feasibility of a laparoscopic approach, albeit these trials compared laparoscopicassisted and not totally laparoscopic gastrectomy.…”
Section: Introductionmentioning
confidence: 99%